The Antecedents of Readiness in Basic Education Management for Transferring Schools from the Ministry of Education - บุตรงามดี ศรีพงษ์ (The Journal of Development Administration Research, 2017)
The objective of this research is to study the antecedents of readiness in basic education management for transferring schools from the Ministry of Education. This research is quantitative research methods. The data come from 600 education division directors; and structure equation modeling is used for analyzing the data. Regarding the results, it is found that local administration organization and potential basic education management have a direct effect on people who access the educational service (R2 = 0.81); meanwhile, local administration organization, potential on basic education management factors and people who access the educational service have both direct and indirect effects on readiness, having an indirect effect via people who access the educational service (R2 = 0.92). The suggestions of this research are; in order to increase basic education management readiness, negotiation and communication among stakeholders are necessary in the changing process.